Customer Loyalty as an Impact of Perceived Usefulness to Grab Users, Mediated by Customer Satisfaction and Moderated by Perceived Ease of Use - Rakha Hendra Maryanto; Thomas Stefanus Kaihatu (Bina Nusantara University, 2021)
The development of Internet users in Indonesia increases quite rapidly each year. This phenomenon makes newonline-based businesses increase. Even when the data show that Grab has got the market share in Indonesia, businesscompetition is ubiquitous. The research analyzed the impact of perceived usefulness and customer satisfactionon customer loyalty in Grab users. It also studied the impact of perceived usefulness on customer satisfactionand the customer satisfaction (moderated by perceived ease of use) as a mediator between perceived usefulnessand customer loyalty. Perceived usefulness and perceived ease of use were dimensions of the TechnologicalAcceptance Model (TAM), which influenced the user’s choice of application usage. The phenomenon of interest inthe research was Grab, as an online-based business application on smartphones. The research applied quantitativeapproach. About 204 samples from 250 respondents were obtained using purposive sampling with questionnairesin Surabaya. The measurement used the 7-category of the Likert scale and adapted from the previous researches.For data analysis, the research used Hayes’s PROCESS model 7, and the reliability and validity tests werealso conducted. The results show that all hypotheses are supported. Perceived usefulness influences customersatisfaction and customer loyalty positively. Then, customer satisfaction and perceived ease of use can work wellas the mediator and moderator. These results contribute to the strategy formulation for business sustainability byGrab or other online-based businesses.